Diagnosis of sulfur availability for corn based on soil analysis - Carciochi, Walter Daniel; Wingaard, Nicolás; Divito, Guillermo Adrián; Reussi Calvo, Nahuel Ignacio; Cabrera, Miguel; Echeverria, Hernan Eduardo (Springer Berlin Heidelberg, 2018)
Different edaphic properties were evaluated to diagnose soil sulfur (S) availability for corn in 15 field experiments as follows: (a) soil sulfate (SO4 −2-S) content at sowing at 0–20 cm and 0–60 cm depths [Sini(0–20) and Sini(0–60)]; (b) soil SO4 −2-S content at V6 corn stage at 0–20 and 0–60 cm depths [SV6(0–20) and SV6(0–60)]; (c) potentially mineralizable S estimations [mineralizable S determined by short-term aerobic incubation (Smineralized), mineralizable N determined by short-term anaerobic incubation (Nan), soil organic matter (SOM), SOM/clay ratio, and SOM/(clay + silt) ratio]; and (d) a combined index between Sini(0–60) and potentially mineralizable S estimations. Three out of 15 sites presented grain yield response to S fertilization (p < 0.1). The average yield response was 1.06 Mg ha−1 for these three sites. From the evaluated predictors, Sini(0–60), SV6(0–60), and Nan were the ones that better estimated the response to S fertilization, showing a linear-plateau relationship (R 2 = 0.68, 0.70, and 0.62, respectively). Values greater than 40 kg S ha−1, 59 kg S ha−1, and 54 mg N kg−1 for Sini(0–60), SV6(0–60), and Nan, respectively indicated no response to S fertilization. All other evaluated edaphic variables presented no relationship, or just a weak one, with S response. The incorporation of S mineralization indexes to the Sini(0–60) model did not improve its performance. Our results indicate that the evaluation of S mineralization has the potential to be used in S fertilization diagnoses.